A Low-Cost PKC-Based RFID Mutual Authentication Protocol - Lili Wei; Qingkuan Dong; Wenxiu Ding (Dianxin kexue)
Based on the PKC-based RFID authentication protocol cryptoGPS which costs the least resource currently,a low-cost mutual authentication protocol which has a flexible key-management and can realize a mutual authentication was proposed.It adopted a new key-management scheme,an optimized fast Rabin encryption algorithm,low Hamming weight modulus and a lightweight stream cipher algorithm Grain V1,moreover,a new low-cost multiplier was designed to achieve the modulus multiplication on large numbers.The security analysis and simulation experiments carried out on Design Complier with Smic 0.25 μm technique show that this scheme is secure enough and in which the tag just needs 4 530 gates,it is suitable for RFID system.